Pickett's charge--the last attack at Gettysburg - Hess, Earl J. (Civil War America (Series), 2001)
Pickett's Charge is probably the best-known military engagement of the Civil War, widely regarded as the defining moment of the battle of Gettysburg and celebrated as the high-water mark of the Confederacy. But as this book notes, the epic stature of Pickett's Charge has grown at the expense of reality, and the facts of the attack have been obscured or distorted by the legend that surrounds them. The book aims to sweep away the accumulated myths about Pickett's Charge.